(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
To mitigate the spread of Corona Virus Disease-19 (Covid-19), monitoring body temperature and performing disinfection are essential preventive measures. Detecting body temperature aids in identifying potential Covid-19 cases, thereby reducing the risk of transmission by limiting contact with others. However, manual temperature screening is prone to inaccuracies and may lead to staff fatigue. Consequently, an automated system for temperature measurement and real-time data display is required to enhance efficiency and reliability. In addition to temperature monitoring, hand disinfection serves as another crucial step in preventing infection. This can be achieved through an automated process that dispenses disinfectant gel upon hand detection. The proposed system integrates these two procedures sequentially: once an individual’s body temperature is assessed and confirmed to be within the permissible range, the disinfection process is triggered. Implementation is facilitated through a gate mechanism equipped with two blades—where the first blade opens upon successful temperature verification, followed by the second blade after automatic hand disinfection. This contactless approach minimizes physical interaction, thereby enhancing safety. The system’s development utilizes an Arduino Mega 2560 microcontroller, integrated with three MLX90614 sensors, three HCSR04 ultrasonic sensors, three E18-D80NK sensors, a relay, a DC motor pump, and two DC blade actuator motors. The permissible temperature threshold can be manually configured. Performance evaluations demonstrate the system’s effectiveness, including successful disinfectant gel dispensing. Furthermore, temperature measurement validation indicates an average deviation of only 0.018% when compared to thermogun readings, affirming the system’s precision and reliability.